Transglycosylation abilities of β-d-galactosidases from GH family 2 - Benešová, Eva; Šućur, Zoran; Těšínský, Miroslav; Spiwok, Vojtěch; Lipovová, Petra (3 Biotech, 2021)
UNLABELLED: The ability to predict the transglycosylation activity of glycosidases by in silico analysis was investigated. The transglycosylation abilities of 7 different β-d-galactosidases from GH family 2 were tested experimentally using 7 different acceptors and p-nitrophenyl-β-d-galactopyranoside as a donor of galactosyl moiety. Similar transglycosylation abilities were confirmed for all enzymes originating from bacteria belonging to Enterobacteriaceae, which were able to use all tested acceptor molecules. Higher acceptor selectivity was observed for all others used bacterial strains. Structure models of all enzymes were constructed using homology modeling. Ligand-docking method was used for enzymes-transglycosylation products models construction and evaluation. Results obtained by in silico analysis were compared with results arisen out of experimental testing. The experiments confirmed that significant differences in transglycosylation abilities are caused by small differences in active sites composition of analyzed enzymes. According to obtained result, it is possible to conclude that homology modeling may serve as a quick starting point for detection or exclusion of enzymes with defined transglycosylation abilities, which can be used for subsequent synthesis of e.g., pharmaceutically interesting glycosides. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13205-021-02715-w.
Keywords: Catalysis; Homology modeling; Hydrolases; Ligand-docking; Carbohydrate family